„Pióropusz” Mariana Pilota: kolekcja stylów i archiwum pamięci kultury - Sławkowa, Ewa (Stylistyka, 2019)
Relying on a broad, anthropological and semiotic understanding of the notion of “style”, the article presents an analysis of the language of the novel with references not only to the linguistic questions such as problems of the Silesia – Great Poland border territory, Pilot’s native dialects, but also to the issues of cultural anthropology such as ethnic stereotypes presented in the novel with their system of values and views of the world. This perspective reveals the style of the novel as hybrydic and hyperbolic. As a document of the author’s attitude towards his own, peasant past and as his reflection upon the place of the peasant paradigm in the Polish culture, as well as the archive of cultural memory (various recognizable historical styles present in the novel such as the epic, romantic, and Gombrowicz-like styles), Marian Pilot’s text appears to be the effect of subjugation of both these spheres to the demands of the poetics of the modern novel. Thus, the elements of both these realms, dialectical and stylistic, have been, in an innovative manner, modified, enhanced and parodied by the author.